Diminishing accessibility of electrophilic nickel(ii) centres due to incorporation of a methylene spacer in the pendant side arm of a series of heterotrinuclear nickel(ii)/sodium complexes: a DFT study using a homodesmotic equation. Issue 17 (15th April 2020) - Bhaumik, Prasanata Kumar; Banerjee, Abhisek; Dutta, Tamal; Chatterjee, Sudipta; Frontera, Antonio; Chattopadhyay, Shouvik
Abstract : The ethoxy groups have a dual effect in hindering the attack of the pseudo-halides on the nickel(ii ) centre and also in stabilizing the complex by intra-molecular interactions. Abstract : Two compartmental N2 O4 donor Schiff bases, H 2 L 1 [ N, N -bis(3-methoxysalicylidene)-2, 2-dimethylpropane-1, 3-diamine] and H 2 L 2 [ N, N -bis(3-ethoxysalicylidene)-2, 2-dimethylpropane-1, 3-diamine], each having inner N2 O2 and outer O4 compartments, have been used to prepare four heterotrinuclear nickel(ii ) complexes [Ni(L 1 )Na(L 1 )Ni(NCS)]·H2 O (1 ), [Ni(L 1 )Na(L 1 )Ni(N3 )] (2 ), [Ni(L 2 )Na(L 2 )Ni]NCS·CH3 OH (3 ), and [Ni(L 2 )Na(L 2 )Ni]ClO4 (4 ). All the complexes have been characterized by elemental and spectral analyses. Single crystal X-ray diffraction analyses have confirmed their structures. In each complex, nickel(ii ) is placed in the inner N2 O2 compartment and sodium is placed in the outer O4 compartment of the respective Schiff base ligand. In complexes 1 and 2, one nickel(ii ) centre is tetra-coordinated (square planar) and the other is penta coordinated (square pyramidal), whereas in complexes 3 and 4, both nickel(ii ) centres are tetra-coordinated. The geometries of complexes 1 and 3 have been optimized without a counterion (denoted as 1 + and 3 + ). The electrophilic nickel(ii ) centre is found to be accessible in complex 1 + and, conversely, it is unreachable in complex 3 +, in agreement with the experimental result. Starting from the hypothetical 1 + complex where both nickel(ii ) centres are tetra-coordinated, the energy change for replacing four methyl groups with four ethyl groups has been computed using ethane and methane to complete the homodesmotic equation. The result is that the intra-molecular interaction of the four ethyl groups favours complex 3 + by Δ E = −26.1 kcal mol −1 .